Factors and causes of rising price of low-cost houses in Penang, Malaysia - Mohamad Syahmi, Mohd Radzi (2017)
depending on the particular location. Urban migrations have caused an increasing demand for residential property in the city, and the scarcity of land for development of landed residential properties in major urban areas in Malaysia, such as Penang, Kuala Lumpur, Selangor and Johor Bahru. This research aims is to understand the theory and the concept of housing in Malaysia which include policies, guidelines, and housing market. Then, this research also to identifying low-cost housing program implementation in Malaysia in general and especially in Penang. Besides that, this research is to analyze the factors and causes of rising price in the implementation of low cost housing in Penang and aspirations to improve its performance in the future. This research adopts a quantitative methods approach. Secondary data analysis is used to achieve the first and second research questions which are the identifying of theory and the concept of housing in Malaysia which include policies, guidelines, projected housing needs, housing market and to identifying low-cost housing program implementation in Malaysia. Descriptive analysis is used to achieve the third research objectives. Descriptive analysis done by using Statistical Package for Social Science (SPSS) software. A total of 71 respondents had answered the questionnaire that was adopted from previous research to ensure the reliability and validity of the findings. The results of the research indicated that the main influencing factors of rising price of low cost house is caused by land and zoning. So, housing develop need to consider this factor to make decision on housing price. The findings are able to benefit various people such as buyers, developers, marketers and government policy regulators, as well as other researchers in order to design a better policy or blueprint that can enhance the development of the housing sector in Malaysia.